Grammatical Appearance of Law in Language Practice of Early 18th Century - E. A. Kudryavtseva (Научный диалог)
The structural and semantic elements of the legislative situation, fixed in the legal acts of the beginning of the 18th century, are considered in comparison with the corresponding structural components of the ancient and Old Russian legislative texts. It is determined that the historical changes in the structure of the legislative situation consist in its significant complication, which manifests itself in the explication of a larger number of elements of the situation, and therefore increases the number of grammatical representations of these elements. The elements of the organization of the law as a text in the period under review are determined: circumstances that caused the need for legislative action; something that should be performed; violation of the prescribed; punishment for violation. Particular attention is paid to the definition of the general structural features of the ancient monuments of law and documents of the early 18th century. It is shown that among such features there is the description of situations, including the element “something that should be performed,” which is the semantic center of the text of the law and is represented by infinitive constructions. In addition, in these texts situation are marked, built on the model of violation of the law → punishment : both in the Old Russian texts and in the laws of Peter the Great’s time they expressed by constructions with conditional clauses. At the same time, in 18th century documents elements of violation of the law → punishment often took a peripheral position in the structure of legislative act. The relevance of the research is seen in the identification of the structural model of the law as a text not on the basis of formal-compositional division, typical to the analysis of documents texts, but on the basis of the determining semantic components and their lexical-grammatical representation, characteristic for certain periods.